Institutional design and polarization. Do consensus democracies fare better in fighting polarization than majoritarian democracies?. Issue 2 (17th February 2023) - Bernaerts, Kamil; Blanckaert, Benjamin; Caluwaerts, Didier
ABSTRACT: It is often claimed that we are living in an age of increasing polarization. Political views, opinions, and worldviews become increasingly irreconcilable ( idea-based polarization ), while at the same time society appears to be getting fractured in antagonistic, opposing camps ( identity-based polarization ). However, a closer look at international datasets reveals that these forms of polarization do not affect all democracies to the same extent. Levels of identity-based and idea-based polarization strongly vary across countries. The question then becomes what can explain these diverging levels of polarization. In this paper, we hypothesize that the institutional design of a country impacts polarization, and that consensus democracies would display lower levels of polarization. Based on a quantitative analysis of the Comparative Political Dataset and Varieties of Democracy data in 36 countries over time (2000–2019), our results show that institutions did matter to a great extent, and in the hypothesized direction. Countries with consensus institutions, and more in particular PR electoral systems, multiparty coalitions, and federalism did exhibit lower levels of both issue-based and identity-based polarization, thereby confirming our expectations. Moreover, we found that consensus democracies tend to be better at coping with identity-based polarization, while the effect on idea-based polarization is smaller.